WITH THE ADVENT OF CHATGPT: HOW TO IDENTIFY STRENGTHS, WEAKNESSES, OPPORTUNITIES, AND THREATS FOR THE FIELD OF EDUCATION AND THE BUSINESS WORLD OF VARIOUS DISCIPLINES - Zaenal Aripin; Ucu Supriatna; M. Syafarudin Mahaputra (KRIEZ ACADEMY : Journal of development and community service, 2023)
Advances in the field of artificial intelligence, particularly with the emergence of generative language models such as ChatGPT, have opened up new opportunities and challenges in a variety of disciplines. This research aims to identify the strengths, weaknesses, opportunities and threats (SWOT) of using ChatGPT in the context of education and the business world from various disciplines. The aim of this research is to explore the impact of using ChatGPT in education and the business world, detailing the advantages and disadvantages of this technology, and designing strategies to exploit its positive potential. This research uses a descriptive qualitative approach to analyze literature, case studies, and subject responses regarding the use of ChatGPT. Data collection involved an in-depth literature review and content analysis of various relevant sources. The research results identified that ChatGPT's strength lies in its ability to provide fast responses, increase operational efficiency, and support decision-making processes. However, drawbacks include inaccurate information, lack of understanding of context, and potential privacy risks. Opportunities are seen in improved customer service, personalized learning, and product innovation. Meanwhile, threats involve the risks of over-dependence, data privacy, and potential misuse of the technology.